2015
DOI: 10.1080/08927022.2015.1032275
|View full text |Cite
|
Sign up to set email alerts
|

On the orientation of N2and CO2molecules adsorbed in slit pore models with oxidised graphitic surface

Abstract: We report grand canonical Monte Carlo studies of nitrogen (77 K) and carbon dioxide (253 K) adsorbed in graphitic slit pores with surface oxygen functionalities. The analysis is focused on the molecular orientation within the adsorption layers and the influence of surface heterogeneity on molecular density distributions. The oxygen-containing surface functionalities act like additional adsorption sites along the graphitic basal plane that interacts also electrostatically with the fluid. Our simulations reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…However, for CO 2 , apart from the adsorption layer close to the pore surface, only one central layer exists with the increase of the pore size. This is because hydrogen bonds can form between the O atom of CO 2 and the surface hydroxyl groups, which leads to CO 2 with an orientation with the O atoms toward the hydroxyl groups . With regard to the rough curved surface of the nanopores, the orientation of CO 2 is complex, thereby the CO 2 is adsorbed in the central layer as a whole phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for CO 2 , apart from the adsorption layer close to the pore surface, only one central layer exists with the increase of the pore size. This is because hydrogen bonds can form between the O atom of CO 2 and the surface hydroxyl groups, which leads to CO 2 with an orientation with the O atoms toward the hydroxyl groups . With regard to the rough curved surface of the nanopores, the orientation of CO 2 is complex, thereby the CO 2 is adsorbed in the central layer as a whole phase.…”
Section: Resultsmentioning
confidence: 99%
“…However, for CO 2 ,a part from the adsorption layer close to the pore surface,o nly one central layer exists with the increase of the pore size.T his is because hydrogen bonds can form between the Oa tom of CO 2 and the surface hydroxyl groups, [33] which leads to CO 2 with an orientation with the O atoms towardt he hydroxyl groups. [34] With regard to the rough curved surface of the nanopores,t he orientation of CO 2 is complex, therebyt he CO 2 is adsorbed in the central layer as aw hole phase.T he structure of the adsorbedC H 4 molecules in silica nanopores changes from as ingle-file chain to two adsorption layers with the variation of the pore size,w hich is in agreementw ith the CH 4 adsorption in CNTs that examined by Zhu and Zhao. [32] Thed ifferences are causedm ainly by the roughness of the surface of the silica nanopores and the different intensity of the interactions between the CH 4 molecules and the silica nanopores compared with those in CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…An explanation for cooperative adsorption of N 2 by CO 2 may lie with considerations of the orientations of CO 2 and N 2 in the adsorbate phase and a tendency toward the minimization of the quadrupolar energy of the adsorbed structure, as has been studied for pure adsorption of CO 2 and N 2 on virtual graphitic slit pores with different degrees of surface oxidation at low temperatures . In this study by Gotzias et al, it was found that both pure CO 2 and pure N 2 preferentially orient vertically to a heavily oxidized pore wall and horizontally in a pristine pore. A repulsion of the tail end oxygen of adsorbed CO 2 away from the surface is physically consistent with the ion-dipole interaction schematic proposed by Little and Amberg, discussed more recently with dry flue gas adsorption on high silica SSZ-13, in which a partial positive charge forms at the tail end oxygen upon forming a stable ion-CO 2 interaction.…”
Section: Models and Methodsmentioning
confidence: 87%
“…Gotzias et al 31 further reported that quadrupolar electrostatic interactions of a CO 2 monolayer shifted the orientations of second layer particles toward a certain direction to maximize lateral CO 2 interaction energy, which obtains the most stable configuration in a less pronounced but repeat pattern of the orientational distribution. Earlier GCMC simulations by Samios et al 35 examined the role of 30% elongated CO 2 molecules to enhance quadrupole−quadrupole interactions and was found to be crucial to sustain highly structured configurations of alternating sublayers of almost normal and almost parallel-tothe-wall molecules.…”
Section: ∑ *mentioning
confidence: 99%
“…Many of the pioneering simulations of surface phenomena involve studies of gases and liquids interacting with carbon solids [1][2][3][4]. Gas-solid or liquid-solid adsorption simulations allow assessing information about the micropore size, the surface area, and some aspects of the surface chemistry of sorbent materials [5][6][7][8]. Porous texture characterization based on gas adsorption is associated with a number of classical and advanced simulation tools performing at the microscopic level such as the density functional theory and Monte Carlo simulations [9][10][11].…”
Section: Introductionmentioning
confidence: 99%